SODA LIGNIN FROM PRE-TREATED BIRCH RESIDUE AND ITS POSSIBLE APPLICATION IN BIOCOMPOSITE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In pulping, the pretreatment of wood has advantages over untreated wood due to enhanced pulp yield and reduced chemical and energy consumption. This study examined the effect of alkaline treatment of birch sawdust on the chemical composition of the sawdust and soda lignin separated from black liquor obtained by soda pulping of the treated birch sawdust. It was found that the alkaline pre-treatment of birch sawdust led to a remarkable removal of hemicelluloses and reduced its mechanical strength. A lower content of acidic and methoxyl groups in the chemical composition of the alkaline lignin obtained by soda pulping of the pretreated sawdust showed the advantage of polycondensation reactions that proceeded during the formation of its primary structure over destruction. The possibility of using the modified soda lignin in a biocomposite was demonstrated. The composite material was fabricated from a blend of recycled polypropylene and polylactic acid, reinforced with ammoxidized wheat straw. The conducted mechanical tests demonstrated the potential of the modified soda lignin to replace more than 30% of the synthetic compatibilizer in the composite formulation without deteriorating the properties of the biocomposite.